The human exposome unraveling the impact of environment on health: promise or reality? - Kelly Polido Kaneshiro Olympio; Fernanda Junqueira Salles; Ana Paula Sacone da Silva Ferreira; Elizeu Chiodi Pereira; Allan Santos de Oliveira; Isabelle Nogueira Leroux; Flávia Bosquê Alves Vieira (Universidade de São Paulo, 2019)
ABSTRACT Considering the innovative nature of the approach to human exposome, we present the state of the art of studies on exposome, and discuss current challenges and perspectives in this area. Several reading and discussion activities were conducted by the Expossoma e Saúde do Trabalhador (eXsat - Group Exposome and Worker's Health), with systematization of the literature in the area published between January 2005 and January 2017, available in the databases PubMed and Web of Science. This comment brings a thematic analysis to encourage the dissemination of the exposome approach for studies in the Public Health area.